Anthropology Inside Out Fieldworkers Taking Notes - Andersen, Astrid Oberborbeck; Dalsgård, Anne Line; Kusk, Mette Lind; Nielsen, Maria; Rubow, Cecilie; Rytter, Mikkel (Sean Kingston Publishing, 2020)
Fieldworkers' notebooks are full of sensations and observations in which the subjectivity of the ethnographer seeps through. Not really science. Much closer to life. Yet in classical anthropology they are invisible to the reader. In this book the focus is reversed, turning Anthropology Inside Out as it explores the vibrant backstage life of field notes. What happens when we put them centre stage? Aimed at both curious novice and experienced practitioner, the chapters read as a catalogue of experimental practices teetering on the edge of the tradition: intuitively observational drawings; notes pervaded with paranoia; collective notetaking; crisis-ridden personal confessions; layers of notes in photographs and archives; old flip-flops that trigger memories in mind and body. This exploration of what field notes are, can do and could be, concludes with a constellation of shimmering notes on notes from Michael Taussig, a meta-commentary on anthropologists' fetishistic relationship with the most personal of professional tools.